IL-17RA-Signaling Modulates CD8+ T Cell Survival and Exhaustion During Trypanosoma cruzi Infection - Tosello Boari, Jimena; Araujo Furlan, Cintia L.; Fiocca Vernengo, Facundo; Rodriguez, Constanza; Ramello, María C.; Amezcua Vesely, María C.; Gorosito Serrán, Melisa; Nuñez, Nicolás G.; Richer, Wilfrid; Piaggio, Eliane; Montes, Carolina L.; Gruppi, Adriana; et al. (Frontiers in Immunology, 2018)
The IL-17 family contributes to host defense against many intracellular pathogens by mechanisms that are not fully understood. CD8+ T lymphocytes are key elements against intracellular microbes, and their survival and ability to mount cytotoxic responses are orchestrated by several cytokines. Here, we demonstrated that IL-17RA-signaling cytokines sustain pathogen-specific CD8+ T cell immunity. The absence of IL-17RA and IL-17A/F during Trypanosoma cruzi infection resulted in increased tissue parasitism and reduced frequency of parasite-specific CD8+ T cells. Impaired IL-17RA-signaling in vivo increased apoptosis of parasite-specific CD8+ T cells, while in vitro recombinant IL-17 down-regulated the pro-apoptotic protein BAD and promoted the survival of activated CD8+ T cells. Phenotypic, functional, and transcriptomic profiling showed that T. cruzi-specific CD8+ T cells derived from IL-17RA-deficient mice presented features of cell dysfunction. PD-L1 blockade partially restored the magnitude of CD8+ T cell responses and parasite control in these mice. Adoptive transfer experiments established that IL-17RA-signaling is intrinsically required for the proper maintenance of functional effector CD8+ T cells. Altogether, our results identify IL-17RA and IL-17A as critical factors for sustaining CD8+ T cell immunity to T. cruzi.